Sistem Informasi Praktek Kerja Industri Pada SMK Islam Sirajul Huda Paok Dandak - Abdul Gani; Wire Baye (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
The data management of students who are carrying out industrial work practices at SMK Islam Sirajul Huda Paok Dandak still in the form of printed documents. In the delivery of information is still on the announcement so that the information can be lost or torn. Information obtained by the Student through the mentor teacher. At the time of the visit to the prakerin location the supervising teacher convey information from the school. This causes the information obtained by students delayed for one month. Information should be received directly by the students when the informs is issued by the prakerin activities committee. In this research developed system of web-based isiting by mentor is moutthly industry-based business information information system of SMK Sirajul Huda Paok Dandak. Analysis method using PIECES method, Design method using Unifed Modeling Language (UML), interface design using CSS, Javascript, Dreamweaver, and xampp as database server. This information system provides information to students of industry practice participants about the format of Prakerin's activity report, visitation schedule of supervising teacher, and timing information on the end of Prakerin's activities. The results of this study indicate the system of technical internship information technology SMK Sirajul Huda provide ease in the delivery of information to students field work practice participants. Information is delivered to 80 percen students in less than a week. 20 percent of those who are not informed are students who do not access the web of the technical internship information system.